Field notes contributed by Beth Proescholdt, Liscomb, Iowa, winter 1983-1984 - Proescholdt, Bethet al (1983)
Field notes were contributed by Beth Proescholdt, Liscomb, Iowa, winter 1983-1984, with nine other observers. A Golden Eagle was documented near Marshalltown, a Pine Grosbeak was documented at a feeder of Robert Wylder in Denver, Iowa, and a Northern Goshawk was documented in Bremer County. Included was a cover letter from Beth Proescholdt to Thomas H. Kent regarding the winter sightings, February 16, 1984. These items were used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1983-1984. Epson - sheet feed